The Effect Of Blended Learning Model To Improve Students’ Writing Achievement During Covid 19 At MAN 1 Aceh Tenggara - Isnaini ramadaniah Skd; Azhary Tambusai; Ahmad Laut Hasibuan (International Journal of Educational Research Excellence (IJERE), 2022)
Blended learning is alternative teaching practice to assist students in improving their performance, which mixed two main elements, namely learning in the classroom and online learning. This study is quantitative research that aims to investigate the effect of the Blended Learning Model on the students’ writing achievement. This research was conducted at MAN 1 Aceh Tenggara on Jln. Iskandar Muda No. 5 Babussalam Student Complex Kutacane, Gumpang Jaya, Kec. Babussalam, Kab. Southeast Aceh, Aceh.  This policy is accompanied by instructions for implementing distance learning or online learning. So, the researcher use blended learning model to improve students writing achievement during covid 19 by implementation of google meet, google classroom, and WhatsApps Group to instructional Media. The population of sample are : XI Mia 1 and XI Mia 2.the experimental group was by XI Mia 1 taught by applying blended learning model and the control group was by XI Mia 2 instructed through the traditional method by lecturing method.The researcher choose this method because very benefit for teacher and student The minimum completeness criteria of English Lesson at MAN 1 Aceh Tenggara = 60. The mean score of students test on pre test = 50,43. The mean score on post test improved become = 78,14 and it reached the minimum completeness criteria score. The calculation of data by using t test and found the tobservation = 2,077 then compared it with ttable = 2,030 of level alpha = 5%. It meant that tobservation was higher that ttable = 26,28 > 2,040.